2022
DOI: 10.1371/journal.pone.0277832
|View full text |Cite|
|
Sign up to set email alerts
|

Bioinformatic analysis and clinical diagnostic value of hsa_circ_0004099 in acute ischemic stroke

Abstract: This study investigates the expression and effect of hsa_circ_0004099 in acute ischemic stroke (AIS). We conducted a case-controlled study that included 40 patients with AIS within 24 hours and 40 healthy subjects during the same period as a control group. Differentially expressed circular RNAs (circRNAs) were obtained using GEO2R, and the expression of hsa_circ_0004099 was verified using RT-PCR. Correlation analysis of the National Institutes of Health Stroke Scale (NIHSS) disease severity score and ischemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Mutations that make RAS more active by impairing GTPase activity prolong downstream signaling, which is associated with cancer cell growth (Kramer‐Drauberg & Ambrogio, 2021). KRAS is one of the top 10 hub genes of the stroke gene array, so it may be involved in the occurrence and development of stroke (Zheng et al, 2022). Based on our results of the serum GTPase assay in the four groups of patients, we found that GTPase expression was down‐regulated in the AF and AF stroke groups but up‐regulated in the AS group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations that make RAS more active by impairing GTPase activity prolong downstream signaling, which is associated with cancer cell growth (Kramer‐Drauberg & Ambrogio, 2021). KRAS is one of the top 10 hub genes of the stroke gene array, so it may be involved in the occurrence and development of stroke (Zheng et al, 2022). Based on our results of the serum GTPase assay in the four groups of patients, we found that GTPase expression was down‐regulated in the AF and AF stroke groups but up‐regulated in the AS group.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations that make RAS more active by impairing GTPase activity prolong downstream signaling, which is associated with cancer cell growth (Kramer-Drauberg & Ambrogio, 2021). KRAS is one of the top 10 hub genes of the stroke gene array, so it may be involved in the occurrence and development of stroke (Zheng et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Results have shown that patients with AIS have lower expression levels of hsa_circ_0004099. The NIHSS score and stroke time were negatively correlated with hsa_circ_0004099 levels, suggesting its potential as therapeutic target in AIS [ 24 ].…”
Section: Circrnas As Diagnostic Biomarkers In Ischemic Strokementioning
confidence: 99%
“…Circular RNAs (circRNAs) have a unique covalent closed loop structure, so their stability is excellent, and their expression is relatively conserved. CircRNAs can participate in a variety of biological processes, among which circRNAs can regulate the expression of their downstream target genes through interactions with RNA-binding proteins [11][12][13]. The cyclic RNA-binding protein QKI is located on human chromosome 6.…”
Section: Introductionmentioning
confidence: 99%